Helminth Diversity In Teleost Fishes From The Area Of The Ukrainian Antarctic Station "Akademik Vernadsky", Argentine Islands, West Antarctica - Kuzmina, T. A.; Dykyy, I. V.; Salganskij, O. O.; Lisitsyna, O. I.; Korol, E. M.; Kuzmin, Yu. I. (Zoodiversity, 2021)
Kuzmina, T. A., Dykyy, I. V., Salganskij, O. O., Lisitsyna, O. I., Korol, E. M., Kuzmin, Yu. I. (2021): Helminth Diversity In Teleost Fishes From The Area Of The Ukrainian Antarctic Station "Akademik Vernadsky", Argentine Islands, West Antarctica. Zoodiversity 55 (3): 251-264, DOI:10.15407/zoo2021.03.251, URL: http://dx.doi.org/10.15407/zoo2021.03.251